The Effect of ROA, ROE, and DER on Stock Prices of Companies Registered in Indonesia Stock Exchange (BEI) During 2021-2024 - Adiansyah Satriyo; Siti Mujanah; AYA Fianto (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER) on the Stock Prices of companies listed on the Indonesia Stock Exchange (IDX). This research uses a quantitative approach with multiple linear regression analysis methods. The research sample was taken using a purposive sampling technique, consisting of 14 companies and consistently listed on the IDX during the 2021-2024 period. The data used is secondary data from annual financial reports and closing stock prices. The results of partial hypothesis testing (t-test) show that the ROA variable has a positive and significant effect on stock prices, the ROE variable has a negative and significant effect on stock prices, while the DER variable has no significant effect on stock prices. The simultaneous test (F-test) results indicate that ROA, ROE, and DER jointly have a significant effect on stock prices. The Adjusted R Square value was 0.345, indicating that 34.5% of the variation in stock prices can be explained by these three independent variables. There limitations of this research are Low R2 score, Samples limitation, and Analytic model.